The origins of agriculture and crop domestication: Proceedings - Damania, Ardeshir B.; Valkoun, J.; Willcox, G.; Qualset, C.O.; International Center for Agricultural Research in the Dry Areas (1998)
We need to understand the past if we are to manage the future; it is therefore necessary to analyze why humans suddenly became sedentary, practised agriculture and evolved civilizations. Wheat and barley together with lentil were among the earliest crops to be domesticated in the arc of land that connects the river valleys of the Euphrates and the Tigris with that of the Jordan. It has become increasingly clear that studies on crop-plant domestication can no longer rely solely on archaeological data but will have to combine the findings of archaeobotanists, archaeozoologists, anthropologists and ecologists to put together all the pieces of the puzzle of how agriculture actually began. A Symposium on the ”Origins of Agriculture and Domestication of Crop Plants in the Near East” was held at the International Center for Agricultural Research in the Dry Areas (ICARDA), 10-14 May 1997. The Symposium was successful in assembling outstanding speakers who delivered very interesting presentations that throw new light on several topics. Their papers are presented in this volume in several sections, grouped under the headings of: Centers of Origin of Crop Plants and Agriculture, Near-Eastern Crop Diversity and its Global Migration, Archaeobotanical Evidence for Agricultural Transitions, Domestication of Crop Plants, Historical Aspects and Crop Evolution, and Conservation of Wild Progenitors. The Symposium heard evidence that the climate was wetter in the Near East than it is today. Given the possible climatic changes we face in the next century or two, we should ask whether we face another quantum leap in the way we grow food. The volume is dedicated to Jack R. Harlan (1917-1998), Plant Explorer, Archaeobotanist, Geneticist and Plant Breeder.